Cardiovascular and metabolic health effects of team handball training in overweight women: Impact of prior experience. (7th November 2019) - Hornstrup, Therese; Póvoas, Susana; Helge, Jørn Wulff; Melcher, Pia Sandfeld; Fristrup, Bjørn; Andersen, Jesper Løvind; Møgelvang, Rasmus; Hansen, Peter Riis; Nybo, Lars; Krustrup, Peter
Abstract : Purpose: We tested the hypothesis that participation in small‐sided team handball training could provide beneficial effects on cardiovascular and metabolic parameters in overweight premenopausal women with special focus on the importance of prior team handball experience. Methods: A 16‐week RCT training intervention was conducted in overweight premenopausal women randomized into three groups: a team handball training group without prior experience (UN; n = 13), a team handball group with prior experience (EXP; n = 10), and an inactive control group (CON; n = 9). Both UN and EXP completed 1.6 ± 0.3 training sessions per week with average heart rates of 84 ± 5 and 85 ± 9% of maximal heart rate, respectively. Cardiovascular and metabolic parameters were assessed before and after the intervention. Results: Compared to CON, UN had significant increases in V O2max  (7 ± 4%) and intermittent endurance performance (26 ± 14%) as well as reduced total fat mass (4 ± 6%), total fat percentage (4 ± 5%), and android fat mass (7 ± 12%), respectively (all P  < .05). Compared to UN and CON, EXP displayed increased left ventricular mass and left ventricular mass index (both P  < .05) after the training period. There were no significant changes between any of the groups in muscle mass, blood lipids, resting heart rate, and blood pressure (all P  > .05). Conclusion: Small‐sided team handball training in overweight premenopausal women resulted in improvement of V O2max and body composition for participants with minimal team handball experience, indicating that prior team handball experience is not a prerequisite for improving physiological parameters of importance for health. Furthermore, EXP displayed cardiac adaptations, including increased left ventricular mass and left ventricular mass index.